Performance evaluation of co-extruded microporous dual-layer hollow fiber membranes using a hybrid membrane photoreactor - Dzinun, Hazlini (Elsevier, 2017)
Hybrid systems with immobilized TiO2 within dual-layer hollow fiber membranes are the most promising set-up for photocatalytic applications because they possess advantages in both the degradation and separation processes. The performance of dual-layer hollow fiber membranes may be maximized using a functional material of high performance as the selective layer. This paper reports the influence of polyethyleneglycol (PEG) as a pore forming agent on the structure and performance of dual layer hollow fiber membranes. Titanium dioxide (TiO2) was used as a photocatalyst in the outer layer of dual layer hollow fiber (DLHF) membranes. DLHF membranes were fabricated via a single step co-extrusion technique and characterized in terms of surface roughness, membrane porosity, hydrophilicity, and cross-sectional and surface morphology. Nonylphenol (NP) photocatalytic degradation and filtration were evaluated using a hybrid membrane photoreactor. The experimental results revealed that DL-PEG/TiO2 membrane increases the NP solution flux, while decreasing the incidence of membrane fouling and allowing for a smoother and more hydrophilic membrane surface. The findings show that the addition of PEG in the inner layer of DLHF membranes may enhance flux performance in the photocatalytic process.